Correlations between maximal strength tests at different squat depths and sprint performance in adolescent soccer players - Keiner, M.; Sander, A.; Wirth, K.; Hartmann, H.; Yaghobi, D. (American Journal of Sports Science, 2014)
For track, field and team sports, many authors advise sport-specific strength training with half and quarter squats instead of parallel squats. Due to the sport-specific argument, higher correlations with sprint performance could be expected for half and quarter squats. Hence, correlations between sprint performance (30 m linear sprint) and both One-Repetition-Maximum (1RM) and 1RM in relation to body weight (REL) in young, elite soccer athletes (n=28) were calculated for different squat depths (parallel, half and quarter). Further isometric maximum strength measurements of the trunk muscles were made. Normally distributed data were analysed using Pearson`s correlation coefficients. For correlation comparisons, Fisher`s z-transformation was computed and the empirical value was compared to the critical value. The data show significant moderate to high correlations for all 3 squat depths (REL) and the performance in linear sprint LS (r = -0.40 to -0.63). No significant differences were found between the correlations of the different squats. However, low to moderate correlations between the maximum trunk strength values and the performance in LS were calculated (r = -0.25 to -0.48). Medium to high correlations between the different squat depths and trunk strength parameters were measured (r = 0.47 to 0.75). Because there is no statistical difference between the correlations of the squat and sprint performances, the researchers` advice is to train and test with the parallel or deep squat because the deeper squat variant requires less weight to generate an adequate stress stimulus for the lower extremities compared with the quarter and half squats.